2001
DOI: 10.1590/s0103-50532001000200012
|View full text |Cite
|
Sign up to set email alerts
|

Volatile substances from male Anastrepha fraterculus wied. (Diptera: Tephritidae): identification and behavioural activity

Abstract: Substâncias voláteis produzidas por machos do gênero Anastrepha foram isoladas previamente de A. ludens e A. suspensa. Ambas as espécies acasalam no período da tarde, liberam compostos similares em diferentes proporções e apenas diferem na produção de monoterpenos. Quando estão em chamamento, os machos de A. fraterculus liberam dois isômeros do sesquiterpeno α-farnesene, três lactonas (anastrefin, epianastrefin e (E,E)-suspensolídeo) e dois monoterpenos (limoneno e (Z)-ß-ocimeno). As glândulas salivares dimórf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 11 publications
2
44
0
2
Order By: Relevance
“…Using different extraction and trapping techniques, it was shown that calling males release compounds similar to those involved in the chemical communication of the Mexican fruit fly, A. ludens, and the Caribbean fruit fly, A. suspensa, including anastrephin, epianastrephin, (E,E)-suspensolide, (E,Z)-a-farnesene, (Z,E)-a-farnesene, limonene, and (Z)-b-ocimene. 107 The salivary glands from virgin mature Females are attracted to faeces and chloroform-methanol extracts of faeces 80 107 However, synthetic compounds were not used in behavioral assays. In another study, Argentine researchers investigated the lekking behavior of male A. fraterculus and found that pheromone calling activity was positively related with copulatory success.…”
Section: Other Selected Topicsmentioning
confidence: 99%
“…Using different extraction and trapping techniques, it was shown that calling males release compounds similar to those involved in the chemical communication of the Mexican fruit fly, A. ludens, and the Caribbean fruit fly, A. suspensa, including anastrephin, epianastrephin, (E,E)-suspensolide, (E,Z)-a-farnesene, (Z,E)-a-farnesene, limonene, and (Z)-b-ocimene. 107 The salivary glands from virgin mature Females are attracted to faeces and chloroform-methanol extracts of faeces 80 107 However, synthetic compounds were not used in behavioral assays. In another study, Argentine researchers investigated the lekking behavior of male A. fraterculus and found that pheromone calling activity was positively related with copulatory success.…”
Section: Other Selected Topicsmentioning
confidence: 99%
“…64 The antimicyns have also other biological properties such as antifungal activity, inhibition of enzymatic activity as well as the ability to induce the death of cancer cells. 65 The main component of this family of peptide alkaloids is the antimycin A 3 , which had been considered as an unique compound until 1988, when analytical investigations using HPLC techniques revealed that this natural product is, in fact, a mixture of the antimycins (+)-A 3a (95) and (+)-A 3b (96). 66 The slight difference between these two nine-membered dilactones relied upon the ester function at C8: (+)-95 is a sec-butyl ester while the (+)-96 is the isobutyl analog.…”
Section: Antimycinsmentioning
confidence: 99%
“…Both racemic 67 and stereoselective synthesis 68 of natural (+)-antimycins A 3b (96) 70 (95), while one approach for (+)-antimycin A 3b (125) was recently reported. 71 Some formal synthesis of these dilactones are also found in the literature.…”
Section: Antimycinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pode haver diferenças no horário de atividade de cortejo (Figura 1) de acordo com a espécie e das condições locais, como luminosidade, temperatura e umidade . Acredita-se que mudanças nos horários de cortejo e cópula estejam envolvidos no processo de especiação em simpatria por alocronia , Miyatake et al 2002 A liberação de feromônio masculino ocorre normalmente com a eversão das pleuras abdominais e da bolsa anal (podendo haver também participação das glândulas salivares - Lima et al 2001), sendo registrada em Anastrepha (Nation 1981, Lima et al 2001, Robacker et al 2009), Toxotrypana (Chuman et al 1987, Heath et al 1996, Ceratitis (Nation 1981, Gonçalves et al 2006, Bactrocera (Perkins et al 1990, Krohn et al 1992, Khoo & Tan 2005, Rhagoletis (Prokopy 1975, Raptopoulos et al 1995, Platyparea (Thibout & Auger 1999, Casaña-Giner et al 2001, Rioxa (Pritchard 1967). Feromônios sexuais femininos também foram registrados em Bactrocera (Mazomenos & Habiotaks 1981, Mazomenos 1984.…”
Section: Comportamento De Acasalamento Em Moscas-das-frutasunclassified